The Hadith on Pursuing Knowledge for Women as a Reflection of Gender Equality in Islamic Jurisprudence - Wakia, Nurul; Ahmad, La Ode Ismail; Sakka, Abdul Rahman (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2024)
The pursuit of knowledge provides women with opportunities to share insights and understanding of religion and social wisdom. This endeavor can enhance faith, support social progress, contribute to various fields that benefit the community, and position women as essential role models for future generations. Specifically, this article discusses the status and obligation of seeking knowledge for women based on the hadiths of Prophet Muhammad (peace be upon him), reflections on women’s pursuit of knowledge, and their role in social life from the perspective of the Prophet. This article employs a qualitative research method based on library studies, using primary sources from literature relevant to the research focus. A thematic approach is applied to interpret the hadiths concerning the obligation to seek knowledge. The findings reveal that education for women in Islam is an obligation equal to that for men, rooted in religious teachings that place knowledge as the foundation of faith and piety. Prophet Muhammad (peace be upon him) emphasized the importance of knowledge for every Muslim, regardless of gender, making it a vital means for understanding religion and enhancing social roles.